Myricanol Inhibits the Type III Secretion System of Salmonella enterica Serovar Typhimurium by Interfering With the DNA-Binding Activity of HilD - Wu, Yang; Yang, Xuefei; Zhang, Dongdong; Lu, Chunhua (Frontiers in Microbiology, 2020)
The type III secretion system (T3SS) consists of a syringe-like export machine injecting effectors from the bacterial cytosol directly into host cells to establish infection. This mechanism is widely distributed in gram-negative bacteria and can be targeted as an innovative strategy for the developing of anti-virulence drugs. In this study, we present an effective T3SS inhibitor, myricanol, inspired by the use of folk medicinal plants traditionally used against infections. Myricanol is a cyclic diarylheptanoid isolated from the medicinal plant Myrica nagi, which is found in South and East Asia. Bioassay-guided fractionation revealed that myricanol inhibited not only the secretion of type III effector proteins of Salmonella enterica serovar Typhimurium UK-1 χ8956 (S. Typhimurium) but also the invasion of S. Typhimurium into mammalian cells, but showed no toxicity to bacterial growth or the host cells. RNA-Seq data analysis showed that the transcription of the pathogenesis-related SPI-1 gene was significantly inhibited by myricanol. Further study demonstrated that myricanol binds physically to HilD and interferes with its DNA-binding activity to the promoters of the hilA and invF genes. In conclusion, we propose that myricanol is responsible for the anti-infectious properties of M. nagi and is a novel T3SS inhibitor of S. Typhimurium through a previously unappreciated mechanism of action.